174k views
3 votes
Please solve the following system of equations by

substitution.

x=y-4
-2x+3y=6

User Peace Wang
by
8.0k points

1 Answer

2 votes
To solve this by using substitution, we have to replace the 2nd equations X with the first
*-2(Y-4)+3Y=6, then we distribute!
*-2Y+8+3Y=6, after that we combine like terms!
*-2Y+3Y+8=6 > Y+8=6, Finally we subtract from both sides!
*Y+8-8=6-8, Which gives us y=-2 as our answer!

Second part!
After that we plug in Y=-2 into the 2ND equation and we solve accordingly!
*-2X+3(-2)=6 >-2X-6=6 > -2X=12
Finally dividing both sides by -2 we get:
X=-6 And Y=-2 as our answers
User Mathan Kumar
by
8.0k points